Cascading style sheets : the definitive guide - Meyer, Eric A. (O'Reilly, 2000)
Cascading Style Sheets (CSS) is poised to make its mark on the Web. With good implementations in Internet Explorer 5.0 and Opera 3.6, and 100% support expected in Netscape's "Mozilla" browser, signs are that CSS is rapidly becoming a useful, reliable, and powerful tool for web authors. CSS is the W3C-approved method for enriching the visual presentation of web pages. Cascading Style Sheets: The Definitive Guide offers a complete, detailed review of CSS1 and CSS positioning, as well as an overview of CSS2. Each property is explored in detail with a discussion of how each interacts with other properties. There is also information on how to avoid common mistakes in interpretation. This book is the first major title to cover CSS in a way that both acknowledges and describes current browser support, instead of simply describing the way things work in theory. It offers both web authors and scripters a comprehensive guide to using CSS effectively. Cascading Style Sheets: The Definitive Guide targets veteran web authors who have already invested thousands of hours in learning HTML and writing web pages and are wondering why they need to learn a brand new language of style. This book supplies those dubious but curious web authors with the information they need to easily implement CSS for their web site. This book also addresses an audience of novice web authors who are already straining to learn all of the tags and attributes of HTML and can benefit now from implementing CSS correctly instead of repeating the mistakes of the past. The author has extensive experience writing about pitfalls and interesting tricks in CSS. He is a member of the CSS & FP Working Group, coordinates the W3C's CSS1 Test Suite, remains active on CSS newsgroups, and edits Web Review's Style Sheets Reference Guide . He has built a widespread reputation as a CSS expert, particularly with regard to his understanding of the intricacies of browser support for CSS. He brings his knowledge and expertise to this book in the form of hints, workarounds, and many other tips for web authors